Advantages of Seoran’s critical speech - Mohammed Dahir, Riyam; Al-Mohammedawi, Ali Abood (Al-Adab Journal, 2021)
Emile Cioran, his philosophical criticism came through the events of his life in terms of his use of the style of Nietzschean and pessimistic fragments, as well as his views on controversial issues from Greek philosophy up to him, and some of Cioran’s criticisms are his criticism directed at the issue of human freedom and unlimited possibilities, either Cioran, his writings revolve around the issue of slavery and human finitude, as he sees the end of all this, death.